2019
DOI: 10.31616/asj.2018.0128
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Balance Correction Following Lumbar Interbody Fusion: A Comparison of the Three Approaches

Abstract: Study Design Retrospective cohort study. Purpose The objective of this study was to compare three widely used interbody fusion approaches in regard to their ability to correct sagittal balance, including pelvic parameters. Overview of Literature Restoration of sagittal balance in lumbar spine surgery is associated with better postoperative outcomes. Various interbody fusion techniques can help to correct sagittal balance, with no clear consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 32 publications
(31 reference statements)
1
36
1
1
Order By: Relevance
“…Each surgeon performed only TLIF or OLIF51 exclusively, which may result in bias. According to previous studies, percutaneous screw system and open pedicle screw system have not been reported to cause any significant difference to lumbosacral sagittal angle 15) . We preserved the contralateral half of the ALL.…”
Section: Discussionmentioning
confidence: 90%
“…Each surgeon performed only TLIF or OLIF51 exclusively, which may result in bias. According to previous studies, percutaneous screw system and open pedicle screw system have not been reported to cause any significant difference to lumbosacral sagittal angle 15) . We preserved the contralateral half of the ALL.…”
Section: Discussionmentioning
confidence: 90%
“…Biomechanical studies have shown that the recovery of LL was beneficial to increase the tension of the anterior longitudinal ligament, which could improve the intervertebral fusion rate and reduce the rate of degeneration of adjacent segments [22]. Another study [23] also found that the key to the recovery of the sagittal balance of the lumbar spine was to restore LL. The recovery of the sagittal balance can reduce the adjacent segmental degeneration caused by the compensated sagittal imbalance and improve the patient's symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TLIF may be preferable in the revision cases, because the lateral access may avoid the postoperative scar tissue on the posterior approach [ 26 - 28 ]. Recently, MIS techniques have gained popularity because these techniques may show favorable results such as reduced blood loss and muscle injury, operative time, and an early postoperative recovery than the traditional open techniques [ 23 , 29 - 34 ].…”
Section: Transforaminal Lumbar Interbody Fusionmentioning
confidence: 99%
“…The surgical oblique view during OLIF is much favorable for the surgeons as compared to LLIF, which only allows a vertical view. Similar to LLIF, OLIF can provide indirect neural decompression and deformity correction [ 29 , 56 , 83 , 84 ]. Meta-analyses have showed that the risks of ipsilateral hip flexor weakness, transient thigh pain, and lumbar plexus injury are lower in OLIF than in LLIF [ 77 , 85 , 86 ].…”
Section: Oblique Lumbar Interbody Fusionmentioning
confidence: 99%